The Effects of In Utero Fetal Hypoxia and Creatine Treatment on Mitochondrial Function in the Late Gestation Fetal Sheep Brain. (29th January 2022) - Muccini, Anna Maria; Tran, Nhi T.; Hale, Nadia; McKenzie, Matthew; Snow, Rod J.; Walker, David W.; Ellery, Stacey J.
Abstract : Near-term acute hypoxia in utero can result in significant fetal brain injury, with some brain regions more vulnerable than others. As mitochondrial dysfunction is an underlying feature of the injury cascade following hypoxia, this study is aimed at characterizing mitochondrial function at a region-specific level in the near-term fetal brain after a period of acute hypoxia. We hypothesized that regional differences in mitochondrial function would be evident, and that prophylactic creatine treatment would mitigate mitochondrial dysfunction following hypoxia; thereby reducing fetal brain injury. Pregnant Border-Leicester/Merino ewes with singleton fetuses were surgically instrumented at 118 days of gestation (dGa; term is 145 dGA). A continuous infusion of either creatine (n = 15 ; 6 mg/kg/h) or isovolumetric saline (n = 16 ; 1.5 ml/kg/h) was administered to the fetuses from 121 dGa. After 10 days of infusion, a subset of fetuses (8 saline-, 7 creatine-treated) were subjected to 10 minutes of umbilical cord occlusion (UCO) to induce a mild global fetal hypoxia. At 72 hours after UCO, the fetal brain was collected for high-resolution mitochondrial respirometry and molecular and histological analyses. The results show that the transient UCO-induced acute hypoxia impaired mitochondrial function in the hippocampus and the periventricular white matter and increased the incidence of cell death in the hippocampus. Creatine treatment did not rectify the changes in mitochondrial respiration associated with hypoxia, but there was a negative relationship between cell death and creatine content following treatment. Irrespective of UCO, creatine increased the proportion of cytochrome c bound to the inner mitochondrial membrane, upregulated the mRNA expression of the antiapoptotic gene Bcl2, and of PCG1-α, a driver of mitogenesis, in the hippocampus. We conclude that creatine treatment prior to brief, acute hypoxia does not fundamentally modify mitochondrial respiratory function, but may improve mitochondrial structural integrity and potentially increase mitogenesis and activity of antiapoptotic pathways.